Preliminary investigation on the use of tank wall reflections to model WEC array effects. (15th September 2018) - Winship, Brian; Fleming, Alan; Penesis, Irene; Hemer, Mark; Macfarlane, Gregor
Abstract: The commercialisation of wave energy converters (WECs) is certain to require the deployment of multiple units in arrays. The collocation of WEC units into an array will lead to hydrodynamic interactions collectively referred to as array effects. Understanding these effects is important for successful developments, concerning energy capture and government approval. To better understand array effects physical experiments and numerical modelling can be completed prior to field deployments. This work explores utilising the reflections from walls to simulate array effects. Including the application and assessment of stereo-videogrammetry for experiments and numerical modelling with Nemoh, a linear potential flow solver. The investigation uses a cylinder fixed in the centre of a wave flume to simulate wave scattering, a component of the hydrodynamics of WECs. The stereo-videogrammetry method uses small buoyant wax particles so that the free surface can be mapped with software from LaVision. It is shown that the stereo-videogrammetry approach applied is able to accurately measure water waves; however there are challenges associated to higher steepness waves and the resulting drift of surface particles. Both the experimental and numerical investigations show great potential in the use of wall reflections to model array effects and correlate well. Highlights: Stereo-videogrammetry method applied to measurement of water free surface gravity waves. Stereo-videogrammetry shown to have measurement accuracy similar to wave gauges for low wave steepness experiments. Wall reflections shown to have an effect on free surface and that walls approximate multiple devices.